2011
DOI: 10.1246/cl.2011.941
|View full text |Cite
|
Sign up to set email alerts
|

2,7-Diborylanthracene as a Useful Building Block for Extended π-Conjugated Aromatics

Abstract: Ir-catalyzed direct diborylation of anthracene produced a 1:1 mixture of 2,6-and 2,7-diborylanthracenes, which could be separated by recrystallization. The SuzukiMiyaura crosscoupling using 2,7-diborylanthracene gave extended ³-conjugated 2,7-disubstituted anthracene derivatives as building blocks for macrocycles. A 1:1 mixture of 2,7-di(4-pyridyl)anthracene and [Pd(dppp)(OTf) 2 ] self-assembled into a [3 + 3] macrocycle.Ir-catalyzed direct borylation of aromatic compounds using bis(pinacolato)diboron is a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Zhang and co-workers reported the C-H/C-H cross-coupling of thiophenes and electrondeficient arenes [44] under previously reported reaction conditions. [45] This reaction was applied to bithiophene (49) and terthiophene (50) in order to introduce pentafluorophenyl groups at the a-positions, providing 51 and 52 in good yields (Scheme 21). The p-extended thiophenes 51 and 52 are known as n-type organic semiconductors.…”
Section: Reports Of C-h/c-h Cross-coupling Reactions (Scheme 20) Are mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and co-workers reported the C-H/C-H cross-coupling of thiophenes and electrondeficient arenes [44] under previously reported reaction conditions. [45] This reaction was applied to bithiophene (49) and terthiophene (50) in order to introduce pentafluorophenyl groups at the a-positions, providing 51 and 52 in good yields (Scheme 21). The p-extended thiophenes 51 and 52 are known as n-type organic semiconductors.…”
Section: Reports Of C-h/c-h Cross-coupling Reactions (Scheme 20) Are mentioning
confidence: 99%
“…The C-H borylation of PAHs such as pyrene, perylene, [49] and anthracene [50] has been reported. For pyrene and perylene, 2,7-diborylpyrene and 2,5,8,11-tetraborylperylene were obtained as the sole products, respectively, while anthracene was converted into a 1:1 mixture of 2,6-and 2,7diborylanthracene.…”
Section: Acenesmentioning
confidence: 99%
“…[9] The next large acene unit suitable for hexagonal design is 2,7-anthrylene, and such frameworks as [6]cyclo-2,7-anthrylene ( [6]CANT, r = 1.97 nm) have been unknown to the best of our knowledge. [10][11][12] The studies of [6]CNAPi ndicated that in order to synthesize such al arge macrocycle, its structure should be modified so that reasonable solubility is maintained. In the courseo fo ur studies of anthracene-acetylene oligomers, [13] we found that bulky mesityl (Mes) groups on an anthracene unit reasonably improved the solubility and stability because those groups protected the aromatic cores from intermolecular stacking and undesired reactions.…”
mentioning
confidence: 99%
“…Based on preceding studies on the iridium-catalyzed borylation of arenes [10][11][12][13][14][15] and fused polyarenes, [9,[16][17][18][19][20][21][22][23][24][25][26] we subjected [4]helicene 1 to mild borylation conditions. Equimolar quantities of the substrate and B 2 pin 2 (pin = pinacolato) and a catalytic amount of [Ir(OMe)(cod)] 2 (5 mol-% Ir) (cod = 1,5-cyclooctadiene) and 4,4′-di-tert-butyl-2,2′-bipyridine (dtbpy) (10 mol-%) were reacted in cyclohexane at 23°C for 18 h. Removal of the volatiles and subsequent column chromatography on silica gel (hexane/DCM from 100:0 to 0:100) resulted in three colorless fractions: unreacted 1 (39 %), a mixture of monoborylated [4]helicenes (51 %), and the last small fraction containing a mixture of bisborylated [4]helicenes (< 8 %).…”
Section: Resultsmentioning
confidence: 99%